A model‐based approach to limb apraxia in Alzheimer's disease. Issue 2 (17th June 2013) - Stamenova, Vessela; Roy, Eric A.; Black, Sandra E.
<x xml:space="preserve">Abstract</x> Limb apraxia is a neurological deficit characterized by an inability to pantomime and/or imitate gestures, which can result from neurodegenerative disorders such as Alzheimer's disease (AD). The major goal of the study was to describe comprehensively the apraxia deficits observed in AD patients and to relate those deficits to general cognitive status, measures of daily activity, and other neuropsychological measures. Limb apraxia was assessed on a variety of conceptual and gesture production tasks in 30 AD patients. As a group, AD patients were impaired across gesture production tasks: of note was the greater impairment in imitation, as opposed to pantomime, which was especially pronounced when patients were imitating with a delay. Imitation performance was best predicted by measures of visuospatial processing, while imitation with delay was best predicted by measures of working memory. In addition, pantomime in response to pictures of tools was less accurate than Pantomime to Verbal Command and holding the tool during performance did not decrease the participants' impairment, while introducing a verbal cue during imitation increased the severity of deficits. Furthermore, investigation into patterns of deficits clearly demonstrated that the nature of limb apraxia deficits observed in AD can be quite heterogeneous and that dissociations between the conceptual and the production system exist. Finally, we also report on significant correlations between general cognitive status and limb apraxia.